2015
DOI: 10.3389/fimmu.2015.00517
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity Responses in the Central Nervous System

Abstract: Immune-mediated tissue damage or hypersensitivity can be mediated by autospecific IgG antibodies. Pathology results from activation of complement, and antibody-dependent cellular cytotoxicity, mediated by inflammatory effector leukocytes include macrophages, natural killer cells, and granulocytes. Antibodies and complement have been associated to demyelinating pathology in multiple sclerosis (MS) lesions, where macrophages predominate among infiltrating myeloid cells. Serum-derived autoantibodies with predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 188 publications
(169 reference statements)
1
9
0
Order By: Relevance
“…It is well established that T cells with specificity for myelin are involved in MS development 46 , however other potential mechanisms of hypersensitivity have also been implicated. MS has, for example, been linked to type II hypersensitivity involving the presence of autoantibodies 47 .…”
Section: Hygiene Hypothesis and Autoimmunitymentioning
confidence: 99%
“…It is well established that T cells with specificity for myelin are involved in MS development 46 , however other potential mechanisms of hypersensitivity have also been implicated. MS has, for example, been linked to type II hypersensitivity involving the presence of autoantibodies 47 .…”
Section: Hygiene Hypothesis and Autoimmunitymentioning
confidence: 99%
“…Neuromyelitis optica (NMO), like MS, is an autoimmune inflammatory disease resulting in demyelination that affects the optic nerve and spinal cord ( Khorooshi et al, 2015 ). Autoantibodies directed at aquaporin-4, a water channel primarily located on brain ependymal cells and astrocytes, are considered the immediate cause, resulting in astrocytic activation, complement fixation, neuroinflammation with cytokine release, immune cell infiltration, and BBB disruption.…”
Section: Physiologic Conditions Disease States and Pharmacologimentioning
confidence: 99%
“…This result is consistent with the pathological findings that the CNS lesions of NMO were mainly infiltrated by neutrophils. 4,15 During the past two decades, more and more evidences had verified that NMO was a distinct disease from MS, 3 especially in the pathological findings. 6,16 Autopsy had revealed that NMO patients had much more severe neutrophil infiltration in the CNS lesions than MS patients, and neutrophil was a very important factor for the inflammatory damage to CNS.…”
Section: Discussionmentioning
confidence: 99%